Mark - Carter, Warren (Wisdom commentary, 2019)
"This commentary on Mark provides feminist interpretation of Scripture in serious, scholarly engagement with the whole text, not only those texts that explicitly mention women. It addresses not only issues of gender but also those of power, authority, ethnicity, racism, and classism"--